Practice of walking, moderate and vigorous physical activity and associated factors in adolescents from a state capital of southern Brazil Prática de caminhada, atividade física moderada e vigorosa e fatores associados em adolescentes de uma capital do sul do Brasil - Silva D.A.S. (2014)
© 2015, Universidade Federal de Santa Catarina. All rights reserved.Physical inactivity is considered a major cause of morbidity and mortality worldwide. The aim of this study was to analyze the association of socio demographic factors, weight status, body adiposity and sedentary behavior with the practice of walking and moderate and vigorous physical activity in adolescents. This cross-sectional study included 631 adolescents (413 girls) aged 14-17 years. A self-administered questionnaire was used to collect data. Boys showed longer time of practice of walking and vigorous activity than girls. Adolescents of high economic level were more involved in vigorous activities. Overweight girls and adolescents showed, respectively, 98 and 138 minutes/week less of practice of walking when compared to boys and normal-weight adolescents. Adolescents with high body adiposity had 100 minutes/week more of practice of walking in relation to adolescents with normal adiposity. In relation to vigorous activity, girls showed 198 minutes/week less when compared to boys. The association of factors investigated in this study with the practice of physical activity in adolescents varies according to the type and intensity of the activity performed.